Osseointegration potential of boron-coated titanium alloy pedicle screw in rabbit spine model - Hidir Ozer; Mehdi Hekimoğlu; Ibrahim Kulac; Ozgur Can Eren; Yeliz Kasko Arici; Haydar Çelik; Ali Fahir Ozer (BMC Musculoskeletal Disorders)
Abstract Background Spinal implants’ longevity is crucial, but titanium alloys, while advantageous, lack strong bone integration. This study aimed to achieve better osseointegration rates by utilizing the ability of boron compounds to transform stem cells in the vertebra into osteoblasts. Method Twenty male albino rabbits were divided into control (n = 10) and experimental (n = 10) groups. Control group received titanium alloy pedicle screws, while experimental group received boron-coated titanium alloy screws. Under general anesthesia, screws were inserted into the L6 and L7 lumbar spines. After 16 weeks, all animals were euthanized for histological examination. Vertebra samples underwent decalcification and H&E staining. Microscopic examination assessed osseointegration, necrosis, fibrosis, and vascularization using a triple scoring system by two blinded observers. Result In the boron-coated titanium alloy group, all subjects exhibited osseointegration, with 50% showing focal, 40% moderate, and 10% complete osseointegration. In the titanium alloy group, 90% showed osseointegration (70% focal, 10% moderate, and 10% complete).The differences between the groups were not statistically significant (p = 0.302). Focal necrosis rates were similar between groups, with 50.0% in the titanium alloy and 60.0% in the boron-coated group (p = 0.653).Fibrosis was absent in the titanium alloy group but present in the boron-coated group, albeit with lower rates of focal fibrosis (20.0%). However, the difference was not statistically significant (p = 0.086).Vascularization patterns showed no significant difference between groups. Conclusion Boron-coated titanium alloy pedicle screws provided osseointegration rates comparable to standard titanium screws and exhibited acceptable levels of necrosis and fibrosis. With stronger biomechanical properties, they could be a better alternative to currently used titanium screws.